High-Performance Structures of Biopolymer Gels Activated with Scleroprotein Crosslinkers - Miroslawa Prochon; Oleksandra Dzeikala; Szymon Szczepanik (Molecules)
The study explores innovative crosslinking processes for biopolymer gel materials using amino acids and ion-redox initiators to significantly enhance their structural and functional properties. Advanced analytical techniques, including FTIR, Raman spectroscopy, XRD, TEM, TGA, DSC, ToF-SIMS, SEM/EDS, GPC/SEC, and elemental analysis, were employed for comprehensive material characterization. The synthesized materials show potential applications in packaging and medicine, particularly for single-use products with short life cycles. Two crosslinking strategies were developed. The first combines gelatin with polyvinyl alcohol (PVA); keratin hydrolysate; and amino acids such as cysteine, hydroxyproline, proline, and histidine. The second employs endogenous cysteine, activated by ion-redox initiators, leveraging its trans-sulfuration ability to form highly stable polymer networks with optimized mechanical and thermal properties. Notably, the synergy between cysteine and potassium persulfate redox initiators proved particularly effective, making this approach attractive for industrial applications. This study introduces novel crosslinking methods and highlights the potential of amino acid-based strategies for designing advanced biopolymer gels with enhanced properties.